The Concept Of Muhammad Iqbal Education Education (Godhead Perspective) - Rini Puspitasari; Achmad Ushuluddin (AIUA Journal of Islamic Education, 2019)
As a poet, philosopher, and reformer of modern Islamic education, Sir MuhammadIqbal actually never specifically wrote about the concept of Islamic education. Is K.G. Saiyidain, in his book Iqbal's Educational Philosophy, which has explained the 8 basic principles of Islamic education in Iqbal's thinking, namely: individual concepts(invide), individual growth, physical and spiritual balance, individual connection with society, individual creativity, intellectual role and intuition , character education, and social education. This article tries to explore further on the first principle, that education must be able to foster the characteristics of 'individuality' (ego / me) of human beings to become a Perfect Man (Insan Kamil). In Iqbal's view, a perfect human being is a human who manifests divine attributes within him, behaves like God. These traits are absorbed and united totally into human beings. Iqbal then used khudi keywords to explain the idea.